Effect of organic fertilization on green cladodes (Opuntia ficus-indica (l.) Mill.) yield in Lerma Valley, Salta, Argentina. Second year - Lozano, Lelia (2013)
The tender cladodes of prickly pear cactus (Opuntia ficus-indica (L.) Mill.) commonly called "nopalitos" are widely consumed in Mexico, whereas in Argentina they are scantily used vegetables. The aim of the present work was to evaluate the effects of the application of three organic manures (hen, cow and sheep) to the production of young cladodes (nopalitos) of prickly pear cactus. The experimental design was a complete randomized block with six replications per treatment. Each experimental unit contained two mother cladodes. They were planted on 4 September 2008, at the beginning of spring. The different treatments (plus an untreated control) were applied a single time at 5 kg per plot at the moment of planting."Nopalitos" were harvested and weighed when they measured 15 cm, from 1 September 2009 until 30 April 2010. Two components of the yield were analyzed: number and weight of the pruned buds. Organic fertilization increased the nopalito production in both weight (p=0.042) and number (p=0.025). The greatest total harvested weight was obtained in the plots fertilized with cow manure (Me= 1961.6 g/plot; RIC=464.5 g/plot), differing statistically from the control plots (Me=1517,7 g/plot; RIC=460,5). The greatest number of harvested nopalitos was obtained in the plots fertilized with cow manure (Me=43 nopalitos/plot; RIC=14.5) and hen manure (Me=44 nopalitos/plot; RIC=14.5 nopalitos/plot), significantly surpassing those found in the control plots (Me=35 nopalitos/plot; RIC= 11.2 nopalitos/plot). This study suggests that the greater benefit of cow manure fertilization also prevails in the second year of the experiment.